Adapting dialectical behavior therapy for outpatient adult anorexia nervosa: a pilot study - Chen, Eunice Y.; Bohus, Martin (The international journal of eating disorders, 2015)
Objective: Anorexia Nervosa (AN) is associated with excessive self-control. This iterative case series describes the augmentation of Dialectical Behavior Therapy (DBT) for outpatient adult AN with skills addressing emotional and behavioral overcontrol. An overly controlled style is theorized to develop from the transaction between an individual with heightened threat sensitivity and reduced reward sensitivity, interacting with an environment reinforcing overcontrol and punishing imperfection. Method: Case Series 1 utilized standard DBT, resulting in retention of 5/6 patients and a body mass index (BMI) effect size increase of d = −0.5 from pre- to post-treatment. Case series 2, using standard DBT augmented with skills addressing overcontrol, resulted in retention of 8/9 patients with an effect size increase in BMI at post-treatment that was maintained at 6- and 12-months follow-up (d = −1.12, d = −0.87, and d = −1.12). Discussion: Findings suggest that skills training targeting rigidity and increasing openness and social connectedness warrant further study of this model and treatment for AN. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:123-132)